Imagining transformative biodiversity futures - Wyborn, C; Davila, F; Pereira, L; Lim, M; Alvarez, I; Henderson, G; Luers, A; Martinez Harms, MJ; Maze, K; Montana, J; Ryan, M; Sandbrook, C; et al. (Springer Nature, 2020)
Biodiversity research is replete with scientific studies depicting future trajectories of decline that have failed to mobilize transformative change. Imagination and creativity can foster new ways to address longstanding problems to create better futures for people and the planet.